2017
DOI: 10.5430/ijhe.v6n2p147
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Tests as a Means of the Students’ Level of Logical Thinking Diagnosis

Abstract: Nowadays pedagogical testing technology has become the basic tool for diagnosis and assessment of the level of students' mastery of learning material. Primarily they allow testing the acquired knowledge and skills in their use as a technology of the definite types of problems solution. Thus, the level of logical reasoning development plays a significant role in the successful mastery of many subjects (mathematical courses in particular). So, the problem of objective and measurable criteria for assessing the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…In connection with thinking skills, Maandig, et al, (2017) found that the DI model can improve the ability to read mathematical symbols and think critically in solving math problems. The results of research by Roman et al, (2017) found that the ability to think logically can be improved through learning and the ability to think logically is needed in every learning. Indriati, (2018) found that the ability to think logically can influence mathematical reasoning and the ability to think logically has a relationship with mathematical reasoning.…”
Section: Resultsmentioning
confidence: 99%
“…In connection with thinking skills, Maandig, et al, (2017) found that the DI model can improve the ability to read mathematical symbols and think critically in solving math problems. The results of research by Roman et al, (2017) found that the ability to think logically can be improved through learning and the ability to think logically is needed in every learning. Indriati, (2018) found that the ability to think logically can influence mathematical reasoning and the ability to think logically has a relationship with mathematical reasoning.…”
Section: Resultsmentioning
confidence: 99%
“…This research shows that students with CS and AS thinking styles have differences in solving mathematical problems in terms of logical reasoning indicators. Students' logical reasoning abilities are needed to help students understand mathematics, improve mathematics skills, and help students' successful mastery of mathematics (Ayuningtyas, Mardiyana & Pramudya, 2019;Roman, Gein & Gerkerova 2017). Understanding students' thinking styles can help teachers formulate the appropriate strategies to improve students' logical reasoning ability in solving mathematical problems.…”
Section: Discussionmentioning
confidence: 99%
“…Students' logical reasoning ability plays a vital role in understanding and improving mathematics skills (Ayuningtyas, Mardiyana & Pramudya, 2019). Roman, Gein and Gerkerova (2017) also argue that logical reasoning ability helps students in the successful mastery of mathematics subjects. Logical reasoning ability is a guideline for operations in mathematics, making mathematics one of the most intensive activities used by students in developing their logical reasoning abilities (Apaydin & Cenberci, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The goal of learning mathematics is to prepare students to be able to deal with changing circumstances in life and in an ever evolving world, through practice acting on the basis of logical, rational, critical, accurate, honest, efficient and effective thinking [1]. The other goal is to mastering mathematics presents specific requirements to the level of the students' logical reasoning [2]. Students' logical thinking ability needs to be improved.…”
Section: Introductionmentioning
confidence: 99%